Postgraduate students’ perceived and actual performance in critical reading skills / Arieff Shamida, Gurnam Kaur Sidhu and Sofwah Md Nawi - Shamida, Arieff; Sidhu, Gurnam Kaur; Md Nawi, Sofwah (Universiti Teknologi MARA, 2021)
The democratization and commodification of education has witnessed an increase in postgraduate education as it is one of the main sources contributing to the advancement of knowledge, technology, and innovation. However, despite the significant rise in numbers, the returns at both the global and national levels have been low due to high attrition and low completion rates among the students. One among the numerous factors cited has been the postgraduate students’ limited competencies in language and research skills. In terms of language, postgraduate students are expected to possess good working knowledge of the English language and be able to read academic literature and write their thesis with acceptable standard of English. Therefore, the main aim of this paper was to assess postgraduate students’ perceived and actual performance in critical reading skills. This study involved a total of 50 postgraduate students from a private university in Malaysia. Data for this study were collected using a questionnaire and a reading test based on the Malaysian University English Test (MUET) Reading Examination Paper. The findings revealed that there was a significant difference between the two performances. Students held a higher perception of their ability when compared to their actual performance in critical reading skills. These results indicate that there is a need for innovative approaches to develop postgraduate students’ critical reading skills so that they can successfully complete their studies within the given duration and graduate on time.